Political context matters: a reflexion about the impact of politics on inclusive education - Sebastião, João (Resurgent Authoritarianism: Sociology of New Entanglements of Religions, Politics and Economies, 2023)
The process of radical transformation of contemporary societies leads us to question the way in which in Europe we face the challenges of inclusive education, and in particular those posed as from the political field. The functioning of educational systems evolves today in a framework of a sequence of crises resulting from the transformations of advanced modernity (Beck, 2009; Lash, 1996; Giddens,1990), reflected by the widening of inequalities associated with market deregulation, global environmental and public health crises, increased digitalization and automation, among others. A second aspect of these transformations concerns the resurgence of nationalism, nativism and authoritarianism with direct impacts on the functioning of democratic regimes and policies to reduce inequalities. The successive crises since 20010 (state budgets, migration, Brexit, covid, war in Ukraine) have shown the fragility of institutional orders (Huang and Höllerer, 2020) in Europe, the disruption of functions taken for granted, and, in several cases, serious setbacks in the process of implementing inclusive education policies. Based on research on the impact of these successive crises on the Portuguese education system, we will analyse how the policy responses of different governments over a period of twelve years have impacted differently on inclusion policies. This analysis will highlight the importance of the policy cycle, how inclusion policies are sensitive to changes in government orientation towards social justice, and how different minority groups are negatively affected by these changes.